Changes in metabolic risk, insulin resistance, leptin and adiponectin following a lifestyle intervention in overweight and obese breast cancer survivors. (5th June 2018) - Travier, Noemie; Buckland, Genevieve; Vendrell, Joan J.; Fernandez‐Veledo, Sonia; Peiró, Immaculada; del Barco, Sonia; Pernas, Sonia; Zamora, Esther; Bellet, Meritxell; Margeli, Mireia; Cirauqui, Beatriz; Muñoz, Montserrat; et al.
Abstract: Adiposity and physical activity are modifiable factors that could be important determinants of breast cancer (BC) prognosis through their effects on endogenous reproductive hormones, chronic inflammation and metabolic changes. Therefore, it is necessary to evaluate whether offering lifestyle interventions to BC survivors could affect the levels of certain biomarkers involved in these mechanisms. We designed a pre–post intervention study offering diet and exercise sessions over 12 weeks to 42 overweight/obese BC survivors. Before and after the intervention, we obtained dietary information, anthropometry and cardiorespiratory fitness (CRF) measurements and blood samples to measure metabolic risk, insulin resistance and adipokines biomarkers. Wilcoxon signed‐rank tests and Spearman partial correlation coefficients were used to compare pre‐ and post‐measurements and assess the correlations between changes in biomarkers and changes in anthropometry and CRF. Breast cancer survivors showed significant improvements in metabolic risk biomarkers and insulin resistance indicators along with a non‐significant leptin decrease and a significant adiponectin decrease. The improvements in metabolic risk biomarkers, insulin resistance indicators and leptin were moderately correlated (0.32 ≤ | r | ≤ 0.55) with the decrease in body mass index and the increase in CRF. Diet and exercise interventions implemented in overweight/obese BC survivors may improve metabolic risk, insulin resistance and leptin biomarkers.